A Review of Skin Banking Guidelines and Standards Worldwide: Towards the Harmonization of Guidelines for Skin Banking in Therapeutic Applications for the Regions under the Asia Pacific Burn Association (APBA). Issue 1 (20th October 2020) - Heng, Wee Ling; Wang, Qi Wei; Sornarajah, Renuka; Tremblay, Jacynthe; Putri, Nandita Melati; Hamid, Suzina Sheikh Ab; Pungrasmi, Pornthep; Wang, Hsian-Jenn; Kim, Dong Chul; Saito, Daizo; Nguyen, Nhu Lam; Sulaiman, Wan Azman Wan; et al.
Abstract: Currently, there are no harmonized guidelines which govern skin banking in the Asia Pacific region. Therefore, skin banks are either unregulated or rely on their nation's legislation or international accreditation to uphold their quality standards. A new set of skin banking guidelines was developed through a comprehensive review and collation of best international practices for the Asia Pacific Burn Association (APBA) members, from donor screening and testing, to skin recovery, processing, storage and distribution, and quality assurance. National regulatory requirements reviewed include the European directives, Australia's Therapeutic Goods Administration and Singapore's tissue banking standards. Further technical and quality management recommendations are referenced from the American Association of Tissue Banks (AATB), the United States Food and Drug Administration standards and guidance documents, various relevant European guides, Japanese Society of Tissue Transplantation guidelines and the Asia Pacific Association of Surgical Tissue Banking. Adapted mainly from the AATB standards, the new Asia Pacific Burn Association Guidelines for Skin Banking in Therapeutic Applications offer a comprehensive manual, addressing: governance and contracts; staff responsibilities; quality management; facilities, equipment and supplies management; donor consent and testing; and recommendations of good practices pertaining to skin recovery, processing, storage and distribution. Besides complementing current generic regulations, they provide technical specifications of major aspects unaddressed in most legislations. This inaugural set of new regional skin banking guidelines would be a start for regional members of the APBA to adopt, and will hopefully culminate in a set of standards so that, in the long run, skin allografts from this region can be of similar quality, which can simplify import process and facilitate the exchange of allografts between members.